Coalitionary proactive aggression and human nature: interdisciplinary approach - Pejković, Kristina (Sociološki pregled, 2026)
The aim of this paper is to provide an interdisciplinary examination of coalitionary proactive aggression in humans, a topic particularly addressed by anthropologist Richard Wrangham within the context of comparative primatology. This type of aggression is most closely aligned with the concepts of organized or collective violence in sociology and manifests as coordinated human actions directed towards achieving a specific goal, often resulting in the injury or killing of individuals, groups, or entire societies. Historical examples of this type of aggression include ritual sacrifices and punishments, massacres, concentration camps, warfare, and actions of state organs such as the military and police, entities that hold a monopoly on violence. The primary question this paper seeks to answer is whether this form of aggression is inherent to human nature. Consequently, a necessary part of the paper is a philosophical-theoretical discussion regarding the (non) existence of human nature and universal properties of human behaviour related to aggression. This is followed by a review of theories on coalitionary proactive aggression encompassing various fields, including primatology, and sociology. Studying this form of aggression is critically important, as its mechanisms are often latent, where aggression may not always be apparent in individual behaviour, yet the cumulative actions of individuals result in violent outcomes.